Enantioselective iron-catalyzed azidation of β-keto esters and oxindoles - Deng, Qing-Hai; Bleith, Tim Manuel; Wadepohl, Hubert; Gade, Lutz H. (Journal of the American Chemical Society, 2013)
The first example of Fe-catalyzed enantioselective azidations of β-keto esters and oxindoles using a readily available N3-transfer reagent is reported. A number of α-azido-β-keto esters were obtained with up to 93% ee, and this methodology also generates 3-substitued 3-azidooxindoles with high enantioselectivities (up to 94%).